HARMONISASI POLA ASUH ORANG TUA DALAM MENINGKATKAN PRESTASI BELAJAR PADA TINGKAT SEKOLAH MENENGAH ATAS - Cheri Surina Ita; Hotmaulina Sihotang (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract : This research was conducted with the aim of seeing the results of the harmonious relationship between parenting styles in increasing the value of learning achievement at the high school level. The research was conducted through a quantitative approach with explanatory methods and descriptive analysis. The data sources analyzed were the results of the fifth semester report cards and questionnaires. From the research conducted, the criteria for harmonization of parenting with parents were very high 41.18%, high 38.82%, sufficient 11.77%, and low  8.23%. For very high student achievement criteria 9.42%, high 32.94%, sufficient 34.12%, and low 23.52% with the interval for the mean score of report cards is  85. The treatment of parents in the family is an important factor in supporting children's formal learning achievement that takes place in the school environment. Keywords : Harmonization,  family upbringing patterns, achievement Abstrak : Penelitian dilakukan untuk mengetahui hubungan harmonisasi pola asuh orang tua dalam meningkatkan nilai prestasi belajar siswa, melalui pendekatan kuantitatif dengan metode explanatory survey dan analisis deskriftif. Sumber data berupa raport semester lima dan angket. Hasil penelitian diperoleh kriteria harmonisasi pola asuh orang tua sangat tinggi  41,18 % , tinggi  38,82 % , cukup 11,77 %, dan rendah  8,23 % . Kriteria prestasi belajar siswa sangat tinggi  9,42 %, tinggi  32,94 %, cukup  34,12 % , dan rendah  23,52 % dengan interval nilai rerata raport 85. Orang tua berperan meningkatkan prestasi belajar siswa. Kata Kunci : Harmonisasi,  pola asuh orang tua,  prestasi belajar